EFEKTIVITAS DINAS SOSIAL DALAM MENANGGULANGI ANAK TERLANTAR DI KOTA SUKABUMI - Nur, Tuah; Alfiah, Arla; Zulfa, Syifa Rizqia; Ridwan, Muhammad Hilmi (JRPA - Journal of Regional Public Administration, 2024)
This research focuses on the problem of increasing the number of abandoned children and the problems of the Social Service in implementing social welfare services for abandoned children in Sukabumi City. Purpose: The purpose of this study was to find out whether there were any innovations made by the Sukabumi City Social Service in tackling neglected children. Method: This method uses a qualitative descriptive method with an inductive approach. The theory used is the Theory of Effectiveness by Duncan (in Steers, 2012: 53) where there are 3 dimensions seen from the achievement of goals, integration and adaptation. Data collection techniques using interviews, observation and documentation.